Concepções de formação e docência dos professores do curso de fisioterapia do Centro Universitário Franciscano - Pivetta, Hedioneia Maria Foletto (2006)
This paper is included in the line of research 'Formation', knowledge and professional development of the Post-graduation Program in Education of the Federal University of Santa Maria. Currently, the institutions of Superior Teaching aim new curriculum proposals in order to fit the professional formation to the demands of the society. Facing this reality, the forming subjects need to search for subsidies to develop their work, which makes mecessary to rethink their practice. In this way, this work brings about the conceptions of formation and instruction of professors in the course of Physics Therapy in the "Franciscan University Center" with a new module teaching proposal. The purpose of the research is to identify and to analyze what conceptions of formation and instruction of professors in the course of Physics Therapy are being built according to the new curriculum. It has, as its methodological reference, the qualitative research and has, as its research instruments, the field daily report and the semi-structured narrative interviews. The subjects of the research are ten professors of the Physics Therapy course,being these, the most involved ones in the feasibility of this teaching model. The interpretation of results occurred by means of a gradual reduction of the qualitative text. The research finding indicate conceptions of formation and instruction that are linked to each other and are being built during the professors' trajectory. These conceptions present strong influence in the project of the course about the professors' thinking and acting processes as well as the professors identify the pedagogical meetings and the practice as privileged spaces of formation and learning in the teaching process.